주요 밭작물 산업의 활성화 방안 - 성명환 (한국농촌경제연구원, 2009)
The purpose of this study is to establish the stable production and distribution system and increase the self-sufficiency ratio by suggesting the future development direction of the upland crops industry, the method to enhance the competitiveness and bring forward the promotion projects of the upland products through the analysis on the current status of the major upland crops industry. The rice cultivation of Korea has decreased every year since 2001. The rice fields are changed to be used for other purpose or are out of cultivation. The grain self-sufficiency rate of Korea is just a 27%. Therefore, it is required to prepare the program to secure food grains stably in preparation for the worldwide scarcity of food grains. Especially, it is highly demanded to improve the self-sufficiency rate of food grains by increasing the production of upland products in the rice fields in order to tackle the problems of the unstable agricultural product supply affected by recent sharp rise of the international grain prices. In other words, we have to make efforts to cultivate the wheat, corn, bean, potato and sweet potato. For this, an appropriate policy guaranteeing the profitability of the upland products for efficient use of the agricultural land is needed. In this study, the regional agriculture promotion policy in the rice paddy is suggested in the aspect of regional rice-paddy farming promotion by linking the industrial policy for the upland crop products with the policies for the rice industry. By means of inducing the production increase of the upland products through the promotion policy, it is purposed to seek the strategies to stabilize the farm income producing upland crop products in the rice paddy, promote the regional agriculture and increase the food self-sufficiency rate. As the strategies of increasing competitiveness of the upland crop products, several programs are suggested such as the organization project of production system in the major producing areas of the upland crop products, the promotion project of the specialized farmers, the farm machine bank project, and the generalization project of agricultural land use. It aims at reducing the farming costs through the expansion of farming areas, mechanization, systematization and modernization of the facilities in the aspects of production, marketing and processing of upland crop products. As strategies to increase the consumption of the upland crop products, the public information project of domestic wheat(Woorimil) and domestic bean product development project are suggested. The purpose of this is to increase the demand for the Woorimil by improving the customers' understanding and implementing various public information activities, and to increase the demand for the domestic beans through developing various new processing products using the domestic beans. In order to activate the upland crop industry, the brand management promotion program is suggested. By fostering the brand product, it is possible to reduce the distribution costs and increase the productivity. The major roles of participators are also suggested such as the government, local self-government, agricultural technology center, agricultural cooperative association, management organizations, and processing companies, etc.